Quercetin and Egg Metallome - Evangelos Zoidis; Athanasios C. Pappas; Michael Goliomytis; Panagiotis E. Simitzis; Kyriaki Sotirakoglou; Savvina Tavrizelou; George Danezis; Constantinos A. Georgiou (MDPI AG, 2021)
The objective of the present study was to investigate the effect of the natural flavonoid quercetin dietary supplementation on the alteration of egg metallome by applying the basic principles of elemental metabolomics. One hundred and ninety-two laying hens were allocated into 4 treatment groups: the control (C) group that was fed with a commercial basal diet and the other experimental groups that were offered the same diet further supplemented with quercetin at 200, 400 and 800 mg per kg of feed (Q2, Q4 and Q8 group, respectively) for 28 days. The diets contained the same vitamin and mineral premix, thus all birds received the same amount of elements since no differences on feed intake existed. The egg elemental profile consisted of As, Ca, Cd, Co, Cr, Cu, Fe, Mg, Mn, Mo, Ni, Pb, Sb, Se, Sr, V, Zn and was determined using inductively coupled plasma mass spectrometry (ICP-MS). Quercetin supplementation altered the elemental profile. Most notably, quercetin altered the element concentrations predominantly in egg shell and albumen. It increased the concentration of Sb while reduced that of Cr and Se in both egg shell and albumen. Moreover, it increased As, Cd in albumen and V in yolk, while compared to the control, reduced As, Cd, Cr, Cu and V and also raised Ca, Fe, Mg and Ni in egg shell. The presence of quercetin led to differentiation of the deposition of certain trace minerals in egg compartments compared to that of hens fed a basal diet, possibly indicating that tailor made eggs for specific nutritional and health requirements could be created in the future.